Pengaruh Kualitas Pelayanan Puskesmas Terhadap Kepuasan Pasien Gigitan Hewan Penular Rabies (GHPR) di UPT Puskesmas Mengwi I Kecamatan Mengwi - I Wayan Suryanata; I Wayan Gede Suacana; A.A. Gede Raka (Public Inspiration : Jurnal Administrasi Publik, 2019)
Abstract The Community Health Center as the Technical Implementation Unit of the District Health Office is responsible for health development in its working area. Community Health Center have the role of organizing health efforts to increase awareness, willingness and ability to live healthy for each population in order to obtain optimal health degrees. The number of cases of Transmission Rabies (GHPR) and the ability of Human Resources (HR) to serve varied and still complaints about services obtained by the community, so the research entitled The Effect of Community Health Center Service Quality on Satisfaction of Transmitted Rabies Animal (GHPR) patients in The Technical Implementation Unit of Mengwi Community Health Center I in Mengwi Subdistrict is important. The formulation of the problems 1. Partially influence the quality of Community Health Center services (tangibles, reability, responsiveness, assurance and empaty) partially to the satisfaction of Transmitted Rabies Animal (GHPR) patients in the Mengwi I Badung Health Center Technical Implementation Unit? (Tangibles, reability, responsiveness, assurance and empaty) simultaneously to the satisfaction of animal bites transmitting rabies (GHPR) in the Mengwi I Badung Health Center Technical Implementation Unit ?. The purpose of this study was to find out and understand the effect of the quality of services of the Mengwi I Technical Implementation Unit on the satisfaction of partial and simultaneous of animal bites transmitting rabies (GHPR) patients. The theory used is the theory of Zeitham Parasuraman-Berry which states that satisfaction is influenced by the quality of services based on 5 dimensions (tangibles reliability, responsiveness, assurance, and empathy). The method used is Random Sampling with a population of 596 and a sample of 100 respondents. Data collection used observation, questionnaire and documentation techniques. The results of this study found that there is a partial effect between tangibles variable of 0.456, reliability of 0.095, responsiveness of - 0.035, assurance of 0.334 and empaty of 0.253 on satisfaction of animal bites transmitting rabies (GHPR) patients. Simultaneously the variable quality of health center services (tangibles, reability, responsiveness, assurance and empathy) had a positive and significant effect on the satisfaction of the animal bites transmitting rabies (GHPR) patients at the Mengwi I Health Center Technical Unit in Mengwi District (P